Identification of lncRNA-miRNA-mRNA Network Involved in Sexual Size Dimorphism of Chinese Tongue Sole (Cynoglossus semilaevis) - Wang, Jialin; Yang, Qian; Hu, Yuanri; Xu, Wenteng; Yang, Yingming; Chen, Songlin; Wang, Na (Frontiers in Marine Science, 2022)
Chinese tongue sole (Cynoglossus semilaevis) is a flatfish species unique to Northeast Asia, exhibiting the typical female-biased sexual size dimorphism (SSD). To explore the possible regulation roles of non-coding RNAs on this phenomenon, whole transcriptomic analysis was performed by using female, male and pseudomale C. semilaevis to identify differentially expressed (DE) long non-coding RNA (DE lncRNAs), miRNAs (DE miRNAs) and differentially expressed genes (DEGs) from brain, gonad, liver and muscle tissues. Most of them were concentrated in the gonad and muscle, and the gene expression patterns of pseudomale were similar with male. The association of DE lncRNAs and target messenger RNAs (mRNAs) were predicted based on antisense, cis-, and trans-regulatory mechanisms, with enriched protein digestion and absorption, cyclic adenosine monophosphate (cAMP) signaling pathway, sulfur metabolism, cell cycle and splicesome (p<0.05). Furthermore, weighted gene co-expression network analysis (WGCNA) was employed to cluster expression patterns of DE lncRNA, and two modules (greenyellow and blue) had the highest positive and negative correlations with growth traits, respectively. Importantly, the female-biased expression in the greenyellow module and the male and pseudomale biased expression in the blue module were observed in the gonad. The gene analysis for DE miRNA revealed 3,034 mRNA-miRNA pairs with the opposite expression patterns. Finally, the lncRNA–miRNA–mRNA network, including 385 DE lncRNAs, 138 DE miRNAs and 456 DEGs, was constructed with cell cycle, cAMP signaling and Ras-proximate-1 (Rap1) signaling. Finally, 78 DE lncRNAs, 12 DE miRNAs, and 13 DEGs were related to the SSD of C. semilaevis. This study described the lncRNA-miRNA-mRNA regulatory network in the SSD of C. semilaevis for the first time. The functional prediction analysis suggested that these DE lncRNA and DE miRNA might be involved in sexual growth differences in fish by regulating several potential growth-related pathways (e.g., cell cycle, cAMP signaling and Rap1 signaling). Further studies related to these non-coding RNAs (ncRNAs) will enlarge our understanding of the regulatory effects of ncRNAs on fish SSD.